SYNTHESIS OF SILICA NANOPARTICLES VIA GREEN APPROACH BY USING HOT AQUEOUS EXTRACT OF THUJA ORIENTALIS LEAF AND THEIR EFFECT ON BIOFILM FORMATION - &et al., AL-Azawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
There is great interest for NPs manufacturing by environmentally friendly and economic manner. The aqueous leaves extract of Thuja orientalis was used to synthesized silica nanoparticles (SiO2NPs) by using two green methods, the first one is the magnetic stirrer method and the second method by using the cold plasma. The XRD pattern for both samples annealed at Ta=600˚C for 1h, while they showed the characteristic of Bragg peaks for poly phases at (001), (010), (10-1), (1-10), (0-12) and (002) for SiO2 triclinic (anorthic). The average crystalline size was calculated by using Scherer’s formula, which was 11.1868 nm in magnetic stirrer method, while the cold plasma method showed amorphous structure. The morphology analysis using atomic force microscopy showed that the grain size was 33.94 and 18.37 nm for magnetic stirrer and cold plasma methods respectively. Fourier Transform Infrared Spectroscopy (FTIR) analysis indicates hydrophilic functional groups in the capping matrix, which can improve the stability of silica NPs. The biofilm inhibition of silica NPs were investigated for two genus of bacteria Staphylococcus aureus and Escherichia coli, the green silica NPs that synthesized by using cold plasma method showed the highest inhibition effect on S. aureus and E. coli  respectively.